High-throughput screen reveals sRNAs regulating crRNA biogenesis by targeting CRISPR leader to repress Rho termination - Ping Lin (Nature Portfolio, 2019)
Small non-coding RNAs (sRNA) regulate bacterial functions by finding nucleic acids and proteins. Here the authors identify PhrS sRNA in Pseudomonas as a positive regulator of CRISPR, and show PhrS acts by binding to CRISPR leader, thereby preventing Rho-mediated transcription termination and promoting anti-bacteriophage immunity.